The Utility of Pain Scale to Assess Verifiable vs Non-Verifiable Pain in United States Emergency Departments - K. Tom Xu; James E. Morris; Christopher Piel (Western Journal of Emergency Medicine, 2020)
Introduction: We sought to examine the utility of self-reported pain scale by comparing emergency department (ED) triage pain scores of self-reported but non-verifiable painful conditions with those of verifiable painful conditions using a large, nationally representative sample. Methods: We analyzed the National Hospital Ambulatory Medical Care Survey (NHAMCS) 2015. Verifiable painful conditions were identified based on the final diagnoses in the five included International Classification of Diseases 9th revision codes. Non-verifiable painful conditions were identified by the five main reasons for visit. Only adults 18 years of age or older were included. The primary outcome variable was the pain scale from 0 to 10 at triage. We performed descriptive and multivariate analyses to investigate the relationships between the pain scale and whether the painful condition was verifiable, controlling for patient characteristics. Results: There were 55 million pain-related adult ED visits in 2015. The average pain scale was 6.49. For verifiable painful diagnoses, which were about 24% of the total visits, the average was 6.27, statistically significantly lower than that for non-verifiable painful conditions, 6.56. Even after controlling for the confounding of patient characteristics and comorbidities, verifiable painful diagnoses still presented less pain than those with non-verifiable painful complaints. Older age, female gender, and urban residents had significantly higher pain scores than their respective counterparts, controlling for other confounding factors. Psychiatric disorders were independently associated with higher pain scores by about a half point. Conclusion: Self-reported pain scales obtained at ED triage likely have a larger psychological component than a physiological one. Close attention to clinical appropriateness and overall patient comfort are more likely to lead to better health outcomes and patient experiences than focusing on self-reported pain alone.